Targeting YAP1/LINC00152/FSCN1 Signaling Axis Prevents the Progression of Colorectal Cancer. Issue 3 (5th December 2019) - Ou, Chunlin; Sun, Zhenqiang; He, Xiaoyun; Li, Xiaoling; Fan, Songqing; Zheng, Xiang; Peng, Qiu; Li, Guiyuan; Li, Xiayu; Ma, Jian
Abstract: As a transcription coactivator, Yes‐associated protein 1 (YAP1)'s role in tumorigenesis is well established. However, the mechanism of YAP1‐regulating long noncoding RNAs (lncRNA) in tumors is still largely unknown. Here, a YAP1 target gene, long intergenic noncoding RNA 00152 (LINC00152), which is highly expressed in colorectal cancer (CRC), is identified. The oncogenic functions of LINC00152 in CRC are demonstrated by a panel of in vitro and in vivo experiments. Further studies reveal the potential downstream mechanisms of LINC00152, which can act as a competing endogenous RNA sponging with miR‐632 and miR‐185‐3p to regulate Fascin actin‐bundling protein 1 (FSCN1) expression and thus promote the malignant proliferation and metastasis in CRC cells. Targeting the YAP1/LINC00152/FSCN1 axis inhibits the progression of CRC. This finding provides a new regulatory model of the "YAP1‐lncRNA" in CRC, which gives rise to a new perspective, "YAP1/LINC00152/miR‐632‐miR‐185‐3p/FSCN1, " to explore the cancer‐promoting mechanism of YAP1 involved in CRC. Abstract : Cancer‐associated long noncoding RNAs (lncRNAs) are emerging as critical regulators in tumorigenesis. Here, a Yes‐associated protein 1 (YAP1) target lncRNA LINC00152 is identified, and a critical role of YAP1/LINC00152/FSCN1 axis in the tumorigenesis of colorectal cancer (CRC) is revealed, which may provide a potential new target for CRC diagnosis and therapy.